Fabrication of Highly Dense Silk Fibroin Biomemristor Array and Its Resistive Switching Characteristics. Issue 4 (24th February 2020) - Kook, Geon; Jeong, Sohyeon; Kim, Mi Kyung; Lee, Sungwoo; Choi, Nakwon; Lee, Hyunjoo J.
Abstract: Development of polymeric memristors is of great interest for wearable and implantable applications because of its flexibility and transparency. One of distinguished polymeric memristor materials is silk fibroin, which is a biodegradable protein extracted from Bombyx mori cocoons. However, fibroin memristors demonstrated earlier show low memory cell density (<100 cells mm −2 ). In this paper, silk fibroin memristors with cell density 25 times higher than that of the previously reported silk fibroin memristors by utilizing wafer‐scale UV photolithography are reported. Unlike shadow masking technique adopted in the previous researches, UV photolithography allows single‐micrometer‐scale alignment between layers to obtain a much denser structure. Memristive characteristics of the silk fibroin memristors are studied under different values of compliance current during SET process with different thickness of silk fibroin films. The ON/OFF ratio of the fabricated memristors is maintained over 1000 s of measurement, and remains the same during bending over a cylinder with a radius of curvature of 1.3 mm. It is shown that silk fibroin remains biocompatible and biodegradable after undergoing the fabrication process. Demonstrated transparency and lightweight characteristics are desirable for electronic components for wearable and implantable systems. Abstract : Photolithographic fabrication of silk fibroin memristors using newly developed set of processes involving only silk‐fibroin‐compatible chemicals allows miniaturization of biomemristor cells in cross‐bar architecture. Flexible, transparent, and biodegradable silk fibroin memristors are now available in high density.